Impact of intensifying primary antibiotic prophylaxis in at-home autologous stem cell transplantation program for lymphoma patients. Issue 7 (6th June 2020) - Rodríguez-Lobato, Luis Gerardo; Martínez-Roca, Alexandra; Moreno, David F.; Gutiérrez-García, Gonzalo; Suárez-Lledó, María; Rovira, Montserrat; Martínez, Carmen; Rosiñol, Laura; Almeida Jorge, Ana Sofía; Pedraza, Alexandra; Cardozo, Celia; Puerta-Alcalde, Pedro; et al.
Abstract: Despite the use of fluoroquinolone (FQ) prophylaxis, neutropenic fever (NF) is the most frequent cause of hospital readmission in ambulatory care programs for patients treated with autologous stem cell transplantation (ASCT). We analyzed the impact of intensifying primary prophylaxis with the addition of piperacillin/tazobactam (PT) to FQ. Between January 2002 and August 2018, 154 lymphoma patients conditioned with BEAM were included (40% received ceftriaxone (Ct) plus FQ and 60% PT plus FQ). NF and hospital readmission were required in 84 vs. 41% ( p  < .0001) and 12 vs. 1% ( p  = .007) of patients within the Ct and PT groups, respectively. The multivariate analysis showed that PT plus FQ retained its independent protective factor for NF (odds ratio (OR): 0.13; p  < .001) and for hospital readmission (OR: 0.07; p  = .01). The use of PT and FQ prophylaxis may effectively prevent episodes of NF and hospitalizations in lymphoma patients managed in our at-home ASCT care model.